دراسة تحليلية لإبداعات موسيقية صيغت على اللحن الشعبي يا حسن يا خولي الجنينة - علي، منتصر القللي أحمد (جامعة حلوان - كلية التربية الموسيقية, 2020)
تعتبر الموسيقى الشعبية المصرية من أهم العناصر المكونة للفلكلور المصري ودائما ما يكون ذلك النوع من الموسيقى بمثابة منجم ثري وزاخر ومعينا لا ينضب ينهل المبدع (المؤلف الموسيقي- الملحن( من عناصرها أو خصائصها الفنية في عملية توظيف تسهم في صياغة بناء موسيقى جديد، ذو نسق فني أعمق، متجاوزا بذلك طبيعة العناصر أو الخصائص الفنية للموسيقى الشعبية المصرية التي اعتمد عليها المؤلف الموسيقي أو الملحن في إبداعه الفني الجديد، مثل اللحن الشعبي "يا حسن يا خولي الجنينة" الذي وظفوه العديد من المؤلفين الموسيقيين والملحنين المصريين في صياغة أعمال موسيقية غنائية وآلية كثيرة، ونظرا لتعدد وتنوع استخدامات هذا اللحن كمطلع للعديد من الأعمال الموسيقية سواء بإحداث أو دون إحداث تعديل، الأمر الذي دعي الباحث للتفكير في حصر هذه الأعمال، وتناولها بالدراسة والتحليل لمعرفة أساليب الملحنين والمؤلفين الموسيقيين المصريين في توظيف هذا اللحن الشعبي في صياغة إبداعات موسيقية متنوعة. هذا وينقسم البحث إلى جزئين: الجزء الأول نظري ويشمل: 1) الدراسات السابقة. 2) حصر الأعمال الموسيقية التي صيغت على اللحن الشعبي "يا حسن يا خولي الجنينة". 3) خصائص الموسيقى والأغاني الشعبية المصرية. الجزء الثاني تطبيقي ويشمل: 1) الخصائص الفنية للإبداعات الموسيقية التي صيغت على اللحن الشعبي "يا حسن يا خولي الجنينة". 2) أساليب توظيف اللحن الشعبي "يا حسن يا خولي الجنينة" في صياغة الأعمال الموسيقية. 3) نتائج البحث وتحليلها والتوصيات. 4) قائمة المراجع وملخص البحث.
Egyptian folk music is considered one of the most important components of Egyptian folklore. This type of music will always be a rich, rich and certain inexhaustible mine. The creator (the composer of music) draws from its elements or artistic properties in an employment process that contributes to the formulation of building a new music, of artistic form Deeper, bypassing the nature of the elements or artistic characteristics of Egyptian popular music on which the author relied on the music or composer in his new artistic creation, such as the popular melody, "O good, O my brothers, the garden." What many Egyptian composers and composers employed in crafting many lyrical and instrumental musical works, and given the multiplicity and diversity of the uses of this melody as an acquaintance of many musical works, whether by creating or without creating an amendment, which called the researcher to think about the inventory of these works, and dealt with them by studying and analyzing to know the methods of composers And the Egyptian musical composers use this popular melody to formulate various musical creations. Research is divided into two parts: The first part includes theoretical -previous studies - Confine the musical works that were formulated on the popular melody, "O good, O my brothers, the garden." - The characteristics of Egyptian folk music and songs The Second Part includes application - The inventory of the musical creations that were formulated on the popular melody, "O Hassan, O Khuli El Geneina". - Methods of employing the popular melody, "O Hassan, O Khali El Geneina" in formulating musical works. - Search results, analysis and recommendations. - A list of references and a summary of the research and research supplements.
Keywords: التراث الشعبي -- الموسيقى الشعبية -- الأغاني الشعبية -- مصر